O sistema em crise ou crise do sistema? repercussões para os negócios imobiliários por seus próprios atores - Filho, Raimundo Silveira (2017)
The crisis that has shaken capitalism in the last ten years has not yet been completely overcome; On the contrary, assumed multiple dimensions, from ethics to politics, from public security to economic blocks, etc. In this sense, this research aims to analyze the crisis conception in the context of real estate business, starting from the following problem: how the concept of crisis emerges and is structured in the context of the business from the conception / perception of students (potential managers) of the Real estate market, in João Pessoa-PB? In methodological terms, a field research was carried out, based on the qualitative approach, distinguishing itself as a descriptive research and with bibliographic procedures. In order to reach the objectives, an individualized semi-structured interview was applied as an instrument of data collection, whose universe concerns the potential managers - Students of the Higher Technology course in real estate business of the Campus João Pessoa (IFPB) - which also fall within the context of Real estate business in this capital (João Pessoa-PB). The sample obeyed the criterion of intentionality and is composed of 05 (five) students. In the data analysis and treatment phase, content analysis was employed. The results show that, as an objective force, the crisis also opens spaces that engender investments in infrastructure and serve to leverage opportunities in the real estate business, such elements are characterized as propulsive springs of contemporary capitalism. The economic dimension of the crisis reveals itself intensely with changes in interest rates and current fiscal policy; In the political field, with the ideological / partisan clash between real estate investments for the public sector that oppose the private sector; And, on the sociocultural side, the crisis is exposed by the lack of motivation of the people to respond positively to the political decisions on the housing deficit. As for dissonance and opportunities in the face of the crisis, the first is about the insecurities of real estate investors motivated by the political-economic crisis, and the second is consolidated with the emergence of new forms of entrepreneurship and new choices of consumers. The conclusion was reached that, in an attempt to escape crises, investing in real estate deals becomes the gravitational field of capitalist economies. Thus, governments move expansionary policies (interest reduction, credit expansion, etc.) to other sectors, with which new collapses arise. Soon the crisis is not overcome, but yes, circumvented.